DOI: 10.20868/upm.thesis.44553
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of regulated deficit irrigation in pistachio (Pistacia vera L.) : water relations and rootstocks influence

Abstract: Madrid 2016Esta tesis se presenta como compendio de publicaciones. Se han editado los articulos originales para establecer una mayor coherencia formal a lo largo del trabajo. Water stress thresholds for regulated deficit irrigation in pistachio trees: Rootstock influence and effects on yield quality.Memmi, H., Gijón, M.C., Couceiro, J.F., Pérez-López, D. (2016). Agricultural Water Management. Impacts of water stress, environment and rootstock on the diurnal behaviour of stem water potential and leaf conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…A field-based study [32] found that the Mateur and Kerman cultivars were more vigorous and had greater chlorophyll and sugar content in leaf when grafted onto P. atlantica than onto P. vera. In more recent studies of plants in pots [18,33,34] and in field conditions [13,35], the highly significant effects of the three rootstocks most commonly used in Spain (P. terebinthus, P. atlantica, and UCB-1) on the growth and water relationships of the Kerman cultivar were described. However, the findings were contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A field-based study [32] found that the Mateur and Kerman cultivars were more vigorous and had greater chlorophyll and sugar content in leaf when grafted onto P. atlantica than onto P. vera. In more recent studies of plants in pots [18,33,34] and in field conditions [13,35], the highly significant effects of the three rootstocks most commonly used in Spain (P. terebinthus, P. atlantica, and UCB-1) on the growth and water relationships of the Kerman cultivar were described. However, the findings were contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [34] concluded that, of these three rootstocks, UCB-1 produced Kerman plants that adapted worst to water stress. Ref.…”
Section: Introductionmentioning
confidence: 99%